2010
DOI: 10.3390/ijms11104063
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Efficacy of Myxococcus fulvus ANSM068 to Biotransform Aflatoxin B1

Abstract: Aflatoxin B1 (AFB1) is commonly found in cereals and animal feeds and causes a significant threat to the food industry and animal production. Several microbial isolates with high AFB1 transformation ability have been identified in our previous studies. The aim of this research was to characterize one of those isolates, Myxococcus fulvus ANSM068, and to explore its biotransformation mechanism. The bacterial isolate of M. fulvus ANSM068, isolated from deer feces, was able to transform AFB1 by 80.7% in liquid VY/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 47 publications
3
39
0
Order By: Relevance
“…Enzymes of diverse origins may also be a useful tool to reduce the aflatoxin contamination of different matrices, as it was suggested by Wang et al (2011). In line with these observations, microorganisms may have advantages with respect to the use of a purified enzyme, since they provide a subset of metabolic pathways that potentially could reduce the aflatoxins levels (Guan et al, 2010).…”
Section: Approaches In the Articles Regarding To Foodssupporting
confidence: 54%
“…Enzymes of diverse origins may also be a useful tool to reduce the aflatoxin contamination of different matrices, as it was suggested by Wang et al (2011). In line with these observations, microorganisms may have advantages with respect to the use of a purified enzyme, since they provide a subset of metabolic pathways that potentially could reduce the aflatoxins levels (Guan et al, 2010).…”
Section: Approaches In the Articles Regarding To Foodssupporting
confidence: 54%
“…Conversely, AFB 1 was found to be stable in the presence of PBS and protease inhibitor cocktail. However, a 100% degradation of AF was observed by Teniola et al (2005) for intracellular extracts of R. erythropolis and Mycobacterium fluoranthenivorans after 8 h as well as a 74% degradation by cells of Flavobacterium aurantiacum in 68 h (Ciegler et al, 1966), meanwhile a degradation of ˂20% was observed for cell extracts of Myxococcus fulvus ANSM068 (Guan et al, 2010).…”
Section: Afb 1 Degradation By Liquid Cultures and Lysatesmentioning
confidence: 92%
“…Subsequent cell lysis was done as previously described in Section 2.3. Heat inactivation of the lysates was done following the method described by Guan et al (2010), and the effect of proteinase K treatment on the lysates was investigated using the method of Smiley and Draughon (2000) by exposing them to 1 mg/ mL proteinase K (Thermo Scientific, South Africa). The obtained lysates were incubated with AFB 1 at 37°C for 3, 6, 12, 24 and 48 h. Extraction, detection and quantification of AFB 1 were done as earlier described in Section 2.3.…”
Section: Heat Inactivation Protease Inhibitor and Proteinase K Treatmentioning
confidence: 99%
“…A number of studies have evaluated intrinsic factors, including carbon source [26,34], nitrogen source [26,34,88], vitamins [26], metals ions [12,34,46,89,90,91,92,93], enzyme inhibitors and promoters [52,89,90,91,92,93,94], initial concentration of mycotoxins [93,95], initial concentration of cells [53,95] and initial pH value [12,14,17,26,31,34,41,46,54,60,88,89,95,96], as well as extrinsic factors, including temperature [12,14,17,25,26,31,34,38,41,46,52,54,60,88,89,95,96], aeriation (shaking rate) [26], oxygen preference [14], as well as pre-incubation [26] and incubation time [34,97]. The experimental designs and optimized biotransformation conditions are summarized in Table 2.…”
Section: Strategies and Methodologiesmentioning
confidence: 99%